2014
DOI: 10.3109/17483107.2014.905642
|View full text |Cite
|
Sign up to set email alerts
|

Technology for hearing loss – as We Know it, and as We Dream it

Abstract: Purpose: Worldwide demand for accessible hearing health technology continues to increase while the numbers of hearing health care specialists are grossly inadequate to meet this demand. Proliferation of innovative technology and the advent of greater access to global connectivity, are providing an opportunity to identify and harness new resources that may change current audiological service delivery methods to maximize access, efficiency and impact. Methods: By searching through the most current literature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
83
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 27 publications
0
83
0
Order By: Relevance
“…Prevention or early identification can reduce the negative consequences of a hearing loss, is usually less expensive and can often be implemented at a community level [13,15]. Costs may also be reduced by using innovative technologies using mobile health or mHealth applications [13,16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention or early identification can reduce the negative consequences of a hearing loss, is usually less expensive and can often be implemented at a community level [13,15]. Costs may also be reduced by using innovative technologies using mobile health or mHealth applications [13,16]. …”
Section: Introductionmentioning
confidence: 99%
“…With the widespread penetration of 4.92 billion mobile phones worldwide, of which more than 3.74 billion are smartphones, mHealth hearing applications are demonstrating promise to improve access to hearing services in low- and middle-income countries (LMICs) [1620]. One such mHealth solution, validated in various contexts, is the hearScreen TM solution that allows a low-cost alternative to conventional hearing screening equipment whilst adhering to required acoustic calibration standards [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…A survey, conducted by Fagan and Jacobs (2009), concluded that there is less than one hearing healthcare professional for every one million people in developing countries. The shortage of professionals combined with a lack of infrastructure and resources, as well as too few training facilities, impedes the provision of adequate hearing healthcare services (Clark & Swanepoel, 2014;Fagan & Jacobs, 2009;Swanepoel, Olusanya & Mars, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Automated audiometry such as the Otogram and AMTAS have the potential to increase hearing healthcare service delivery because they do not require trained professionals to conduct the assessment procedures (Margolis et al, 2010;Ho et al, 2009). As such, paraprofessionals can be trained to facilitate audiological assessments, because automation greatly reduces the complexity of these services (Clark & Swanepoel, 2014;Swanepoel, Clark, Koekemoer, Hall, Krumm, Ferrari, McPhearson, Olusanya, Mars, Russo & Barajas, 2010b). As a result, hearing healthcare professionals are able to focus their attention on management, counselling and intervention (Swanepoel et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation